Perancangan Dan Pengembangan Sistem Informasi Akuntansi Penjualan Berbasis Web Pada Jambi Herbal Shop - Chrisnawati, Lily; Devitra, Joni (LPPM Universitas Dinamika Bangsa, 2020)
Research on the Jambi Herbal Shop conducted to analyze and design the existing system, in orderto overcome the problems associated with the sale and stock of goods of faced by Jambi HerbalShop as well as the calculation of profits. The research method is done by using the method ofanalysis of the interviews, library research and design method. The results showed some of theweaknesses of the existing system is still using manual system for recording and sales. It isconsidered less effective and efficient because it requires a long time in the sales process and thecalculation of profits in that way. Based on the analysis of the author, the author merancangan anaccounting information system to solve the existing problems that generated an accountinginformation system that is capable of displaying trading company income statements, statementsof accounts receivable, goods report, sales reports and accounts payable so as to accelerate thesales process and increase sales there.